Community-Based learning and the work of literature (Anker Pub. Co., 2007)
This book examines how community engagement reimagines academic work in the humanities, proposing new methodological and theoretical approaches to scholarship and pedagogy in literary studies. The chapter contributors--scholars of English and foreign language literature and cultural studies--respond to three questions: How can literary theory inform community-based learning (CBL)? How does community service transform our assumptions about literature and the literary aspects of everyday life? And finally, in what ways do current readings in cultural studies extend to the question of civitas, or the creation of a vibrant community life? By answering these questions, the contributors move literary studies beyond the lecture hall and certified competency in the reading of texts and toward the formation of learning communities without walls or borders. These humanities-based learning communities revise our conceptions of the human condition, construct an expanded and active sociological imagination, encourage compassion, and address issues of social justice. Written for faculty and staff in literature and humanities programs at all types of institutions, this book provides innovative ways to incorporate CBL into classroom experiences.